Mutations in genes encoding innate immune molecules identified in bladder cancer samples as potential biomarkers for immunotherapy with BCG and agonists - de Queiroz, Nina Marí Gual Pimenta; Mambelli, Fabio; Silva, Bruno Marques; Oliveira, Sergio Costa (Frontiers in Urology, 2023)
Bacillus Calmette–Guérin (BCG) immunotherapy for the treatment of bladder cancer (BC) depends on the recognition of bacteria by extracellular toll-like receptors (TLRs) or the detection of mycobacterial DNA by endosomal TLRs or the cGAS-STING pathway. Agonists related to these innate immune pathways have been developed as adjuvants to potentiate the effects of immunotherapy. As innate immune pathways are important for the action of BCG and other agonists proposed for BC therapy, we decided to investigate the presence of mutations in the main receptors of these pathways. The Cancer Genome Atlas (TCGA) database was screened to identify BC-related mutations (apart from oncogenes), targeting, in particular, TLRs, the adaptor molecule MyD88, and the cGAS-STING (cyclic GMP-AMP synthase-stimulator of interferon genes) immune pathway. Among 1,724 BC entries, 103 mutations were identified in 80 affected cases in the cohort. TLR9 and TLR10 ranked among the most frequent mutated genes observed in the affected cases in our search (13 mutations each). Through all analyzed data, the search for MYD88 gene recovered only 1 mutation input in the database. Mutations in the STING and cGAS genes were found in one and four cases, respectively. We also evaluated clinical data, including the pathologic stage of BC, and gene expression from 103 mutations entries. This article attempts to highlight the relevance of mutations in genes coding for innate immune molecules in BC samples as potential biomarkers to predict individual disease outcome, and specifically to help find the appropriate treatment for each person in the future.